Pelaksanaan Pembelajaran PJOK Materi Beladiri Pada Masa Pandemi Covid-19 Tahun 2021 (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the implementation of PE learning in high school martial arts in Temanggung Regency. This study uses a qualitative method. Data collection techniques using observation, interviews and documentation. The sampling technique used total sampling, namely that there were 15 high schools that were the object of the study. The results showed that many schools planned martial arts learning, but not all of them continued with learning activities, only 7 schools implemented learning, and 9 schools carried out assessments. The conclusion is that 14 schools carry out learning planning, 7 schools that continue to learning activities are classified as good, 7 schools carry out learning well, and 9 schools carry out assessment activities well. Teachers who do not carry out martial arts learning because of the lack of personal potential of teachers and limited infrastructure.